Greening Your Way to Profits: Green Strategies and Green Revenues - Huang, Zijie; Cao, June; Pan, Lei (2024)
We examine hot-debated but underexplored questions of whether and how green strategies affect corporate green revenues. Using a generalized Difference-in-Differences (DiD) framework, we find that green strategies significantly enhance corporate green revenues in the presence of China's Emission Trading Scheme (ETS) pilot. This is consistent with the Porter Hypothesis. Our mechanism analyses document that green strategies increase green revenues by improving green quality and catalyzing environmentally friendly transformation. This study has important implications for policymakers and practitioners, offering new insights into the intended consequences and real outcomes of environmental regulations.